Do domestic firms benefit from FDI?: evidence from Korean manufacturing industries - Tae Seung Kim; Hun-Koo Ha; Jin Kook Lee (Journal of International Logistics and Trade, 2008)
FDI is considered to be a meaningful component for the economic growth of a country. But, it has not been proven clear that the effect of FDI is really beneficial in a host country regardless of the state of the countries. This paper tries to provide an evidence of the effect of FDI in developing country. To do this, we relate industry level value-added to inward and outward FDI stocks in Korea in a production function framework. Especially we divide inward FDI into FDI on the Greenfield projects and FDI for M&A. The results show that the effect of inward FDI as a whole on productivity is not statistically significant, though we can presume that the direction is positive, whereas the effect of outward FDI is strongly negative, and is statistically significant. But the effects of inward FDI by the characteristics of FDI are not differentiated.